THE EFFECTS OF FINANCIAL DEVELOPMENT AND FINANCIAL INCLUSION ON POVERTY ALLEVIATION - Taiwo, Bello Hassan (JURNAL EKONOMI AKUNTANSI MANAJEMEN AGRIBISNIS, 2025)
This study investigates the impact of financial development and financial inclusion on poverty alleviation. The study aims to contribute to the existing literature on the role of financial development and inclusion in reducing poverty. Using a quantitative method approach, this study analyzes the relationship between financial development, financial inclusion, and poverty reduction. The findings of this study reveal that financial development and financial inclusion have a significant positive effect on poverty alleviation. Specifically, the results show that increased access to financial services, such as savings accounts, credit, and insurance, can help reduce poverty by providing households with the financial tools needed to manage risk, invest in education and healthcare, and accumulate wealth. The study's results have important implications for policymakers and practitioners seeking to promote financial development and inclusion as tools for poverty reduction. The findings suggest that policies aimed at increasing access to financial services, improving financial literacy, and promoting financial inclusion can be effective in reducing poverty. Overall, this study provides new insights into the relationship between financial development, financial inclusion, and poverty alleviation, and highlights the importance of considering financial development and inclusion in poverty reduction strategies.